The Reliability and Quality of Short Videos as a Source of Dietary Guidance for Inflammatory Bowel Disease: Cross-sectional Study - Zixuan He; Zhijie Wang; Yihang Song; Yilong Liu; Le Kang; Xue Fang; Tongchang Wang; Xuanming Fan; Zhaoshen Li; Shuling Wang; Yu Bai (JMIR Publications, 2023)
BackgroundDietary management is considered a potential adjunctive treatment for inflammatory bowel disease (IBD). Short-video sharing platforms have enabled patients to obtain dietary advice more conveniently. However, accessing useful resources while avoiding misinformation is not an easy task for most patients. ObjectiveThis study aimed to evaluate the quality of the information in IBD diet-related videos on Chinese short-video sharing platforms. MethodsWe collected and extracted information from a total of 125 video samples related to the IBD diet on the 3 Chinese short-video sharing platforms with the most users: TikTok, Bilibili, and Kwai. Two independent physicians evaluated each video in terms of content comprehensiveness, quality (rated by Global Quality Score), and reliability (rated by a modified DISCERN tool). Finally, comparative analyses of the videos from different sources were conducted. ResultsThe videos were classified into 6 groups based on the identity of the uploaders, which included 3 kinds of medical professionals (ie, gastroenterologists, nongastroenterologists, and clinical nutritionists) and 3 types of non-medical professionals (ie, nonprofit organizations, individual science communicators, and IBD patients). The overall quality of the videos was poor. Further group comparisons demonstrated that videos from medical professionals were more instructive in terms of content comprehensiveness, quality, and reliability than those from non-medical professionals. Moreover, IBD diet-related recommendations from clinical nutritionists and gastroenterologists were of better quality than those from nongastroenterologists, while recommendations from nonprofit organizations did not seem to be superior to other groups of uploaders. ConclusionsThe overall quality of the information in IBD diet-related videos is unsatisfactory and varies significantly depending on the source. Videos from medical professionals, especially clinical nutritionists and gastroenterologists, may provide dietary guidance with higher quality for IBD patients.